2014
DOI: 10.1111/epi.12856
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery in patients with bilateral temporal lobe seizures: A systematic review

Abstract: SUMMARYWe explored the association between magnetic resonance imaging (MRI) lesion, degree of seizure laterality on intracranial electroencephalography (iEEG), and seizure outcome in patients with ambiguous or presumed bilateral temporal lobe epilepsy (BiTLE) on scalp EEG. We systematically reviewed the literature using Embase and MEDLINE up to May 31, 2012. Patients with bilateral iEEG, temporal lobe surgery, and follow-up ≥1 year were included. We undertook three separate analyses on patients whose scalp EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 46 publications
1
44
0
6
Order By: Relevance
“…From the early stage of epilepsy surgery, bilateral TLE has been diagnosed on the basis of clinical semiology and findings from MRI and scalp EEG [6]. However, it is not rare for patients with TLE to present with bilateral temporal lobe epileptiform discharges on scalp EEG, and only 11.5% of patients were true bilateral TLE [3]. Therefore, intracranial electrode EEG is commonly used in the diagnosis of bilateral TLE, although the use of this method is not obligatory.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the early stage of epilepsy surgery, bilateral TLE has been diagnosed on the basis of clinical semiology and findings from MRI and scalp EEG [6]. However, it is not rare for patients with TLE to present with bilateral temporal lobe epileptiform discharges on scalp EEG, and only 11.5% of patients were true bilateral TLE [3]. Therefore, intracranial electrode EEG is commonly used in the diagnosis of bilateral TLE, although the use of this method is not obligatory.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Loesch et al [13] performed unilateral ATL in 11 patients with bilateral TLE, with 10 (90.9%) achieving postoperative Engel level I-II seizure control, and Cukiert [15] reported that all 9 patients with bilateral TLE who received unilateral ATL attained Engel level I-II seizure control 5-10 years after the procedure. Aghakhani et al [3] reviewed 1,403 patients with ambiguous or presumed bilateral TLE on scalp EEG, determining that 1,027 (73%) exhibited unilateral TLE on intracranial EEG and underwent unilateral ATL. Of these patients, 58% achieved Engel class I control, and 9% achieved an Engel class II outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations